Pelembagaan Mediasi Desa dan Sinergi Membangun Sistem Peradilan - Kokotiasa, Wawan (LP. Ma'arif Janggan Magetan, 2023)
Institutionalization of village mediation is a strategic and synergistic endeavor with efforts to build a justice system in Indonesia. Especially in the perspective of access to justice for people in rural areas who experience disputes. Based on Law Number 6 of 2014, there are regulations that provide space and creativity for villages to institutionalize village mediation as